2015
DOI: 10.21608/ejceh.2015.253714
|View full text |Cite
|
Sign up to set email alerts
|

Some Studies on Ornithobacterium Rhinotracheale (Ort) in Broiler Chickens

Abstract: Affected 100 flocks revealed chronic whitish diarrhea. Consistent gross pathological lesions recorded were congestion and consolidation of lungs, hemorrhages in trachea, congestion and hemorrhages in liver, splenomegaly and necrotic foci on the kidneys, mortality in various flocks ranged from 3.7 -15% detailed isolation and biochemical studies revealed that Ornithobacterium Rhinotracheale was responsible for this wide spread respiratory problem. Five ORT isolate positive PCR implications were pre elicited to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
0
0
Order By: Relevance
“…Ellakany et al (2019) revealed ORT isolates were detected in Broilers and layers with a percent of 11.66%and closely related to Asian, European, and American strains (98%-100%). Masoud et al (2015) showed a similarity percent of 94%-98% among the selected five broiler's ORT strains and some Asian, and American ones. Thieme et al (2016) when compared the results of 16S rRNA gene sequencing and multilocus sequence typing (MLST) in 65 isolates of ORT, they demonstrated identity ranging 85.1%-100%.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Ellakany et al (2019) revealed ORT isolates were detected in Broilers and layers with a percent of 11.66%and closely related to Asian, European, and American strains (98%-100%). Masoud et al (2015) showed a similarity percent of 94%-98% among the selected five broiler's ORT strains and some Asian, and American ones. Thieme et al (2016) when compared the results of 16S rRNA gene sequencing and multilocus sequence typing (MLST) in 65 isolates of ORT, they demonstrated identity ranging 85.1%-100%.…”
Section: Discussionmentioning
confidence: 96%
“…In Egypt, Youssef and Ahmed (1996); El-Gohary (1998), El-Gohary and Awaad (1998); El-Gohary et al (1998); El-Gohary and Sultan (1999); Abd El-Avian disease Ghany (2000) isolated ORT from broiler, turkey, and layer flocks either alone or concomitantly with other organism as well as other many studies were done on isolation, characterization, and treatment of ORT (Amal, 2002;Shihata and Ibraheem, 2004;Shahata et al, 2006;Attia, 2008;Elbestawy, 2010;Hegazy et al, 2015;Masoud et al, 2015;El-Abasy et al, 2016;Ellakany et al, 2019;Hassan et al, 2020). Vandamme et al (1994) described ORT bacterium as highly polymorphic Gram-negative rod, non-motile, non-spore former in family Flavobacteriaceae.…”
Section: Introductionmentioning
confidence: 99%